Business opportunities Sandra Handicraft: dropship / Tracy Stanly - Stanly, Tracy (2022)
There are several reasons to why I choose this line of product to be my business opportunity project. I decided to be the dropship of Sandra Handicraft I can see a huge opportunity can be grabbed in the business. Other than that, the reason why 1 choose this kind of business is because I would like to support the local product. Sandra Handicraft also provides various types of of high-quality of their goods at the best prices and have a various style and design at the best prices and low as RM 10. Although the price is low, Sandra Handicraft still maintain high-quality products for their customers. In this pandemic, I am thinking that this project are actually a good opportunity for me to try embrace the new norm and venture into the online businesses. Everything are pretty much can be done online nowadays and majority of people can do online shopping. So with that in mind, everything from marketing to transaction will be done online.